Tinjauan Hukum Tentang Administrasi Pendaftaran Tanah Sistematis Lengkap Di Kantor Pertanahan Kabupaten Dairi - Herman Brahmana; Theresia Argatha Nainggolan; Zuniati Gea; Agus Irawan (UNES Law Review, 2023)
Because there is still a lot of land that has not been registered, legal certainty regarding community rights to land is important in land dispute situations. The Minister of Agrarian Affairs issued Regulation Number 6 of 2018 concerning Complete Systematic Land Registration. This is research that aims to find mass certification procedures for government land, as well as factors that support and hinder Complete Systematic Land Registration (PTSL) efforts in Dairi Regency. Legal frameworks are used first in field research, then social and behavioral data. Minister of Agrarian and Spatial Planning Regulation Number 6 of 2018 states that certificates obtained in Dairi Regency through Complete Systematic Land Registration (PTSL) fulfill the land registration requirements. Program implementation still faces challenges related to location distance. Due to a lack of public awareness of the program, PTSL was only partially implemented, with a small number of surveyors and little public enthusiasm. The National Land Agency needs to involve the community more and carry out further inspections to reduce obstacles.